2010
DOI: 10.1111/j.1469-8749.2010.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of classifications between parents of children with cerebral palsy aged 2 to 6 years and therapists using the Gross Motor Function Classification System

Abstract: AIM The aim of this study was to determine the agreement and reliability of parent report using a lay version of the Gross Motor Function Classification System (GMFCS) among children with cerebral palsy in the two youngest age bands. METHOD Data were obtained from the Canadian section of the Movement and Participation in LifeActivities of Young Children study database. One hundred and thirty-two parents of two groups of children participated: children aged 2 to 4 years (35 males, 26 females; mean age 3y 2mo; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
3
27
1
1
Order By: Relevance
“…The children classified as levels IV and V require the use of assistive technology (manual or powered wheelchair), which depends on contextual factors 12 such as accessibility to these resources, architectural barriers, as well as personal factors including acceptance of colleagues and family 12 . The cost of a wheelchair in Brazil is high, however, the Brazilian government has increased funding for the Health System to provide free wheelchairs at national, state, and municipal levels 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The children classified as levels IV and V require the use of assistive technology (manual or powered wheelchair), which depends on contextual factors 12 such as accessibility to these resources, architectural barriers, as well as personal factors including acceptance of colleagues and family 12 . The cost of a wheelchair in Brazil is high, however, the Brazilian government has increased funding for the Health System to provide free wheelchairs at national, state, and municipal levels 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The GMFCS Family Report Questionnaire 9 has been used by parents of children with CP to classify gross motor function and has been shown to be consistent with those of health professionals in studies conducted in both Canada 9 and the UK 10,11 . Such classification may differ due to children's varying performance in relation to methods of mobility 12 in different environments (home, school, hospital). Families will almost certainly know their children's ability across a broader range of settings 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The GMFCS E&R translation into Brazilian Portuguese made in accordance with the ones suggested by Center For Childhood Disability Research (CanChild) and made available on their website * was conducted in 2010 by a group of occupational therapists and one neurologist 7 . The validity and reliability of the original version of the GMFCS have been extensively studied and well established among health professionals in different countries (physical therapists, pediatricians, orthopedists, physiatrists, and occupational therapists) 6,8,9,10 , and parents 8,[11][12][13][14][15] , which is also beginning to occur with the extended and revised version (GMFCS E&R) 16 . The GMFCS can easily be incorporated into clinical practice, allowing comparisons of children accompanied by different clinicians with similar functional levels, and also can predict the gross motor function of children with cerebral palsy 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As recent studies have shown, families will almost certainly know their children's ability best in a broader range of settings; the family assessment for the GMFCS may be the most suitable method of data collection for registries worldwide. 6,7 This commentary is on the article by Ramstad et al on pages 1013-1018 of this issue.…”
mentioning
confidence: 99%